2020
DOI: 10.1097/md.0000000000019556
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and effectiveness of using a wrist heart rate monitor as a telerehabilitation device in cardiac patients

Abstract: Background: Telerehabilitation in cardiology has the potential to become the alternative to regular outpatient cardiac rehabilitation. Our study focuses on the wrist heart rate monitor as a telerehabilitation device, defines detected limitations, and compares results between home-based and regular outpatient rehabilitation methods, related to physical fitness, quality of life, and training adherence. The study design was a randomized controlled trial. Methods: Eligible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
140
2
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(156 citation statements)
references
References 31 publications
2
140
2
12
Order By: Relevance
“…The results of the 8-week effect of HBCT intervention created the expected significant improvement in cardiorespiratory fitness by almost 8%, which corresponds to studies where the usual effect of exercise was around 7-15% [30][31][32]. It is necessary to mention that cardiorespiratory fitness is one of the independent factors predicting cardiovascular mortality, morbidity, and rehospitalization [33].…”
Section: Discussionmentioning
confidence: 66%
“…The results of the 8-week effect of HBCT intervention created the expected significant improvement in cardiorespiratory fitness by almost 8%, which corresponds to studies where the usual effect of exercise was around 7-15% [30][31][32]. It is necessary to mention that cardiorespiratory fitness is one of the independent factors predicting cardiovascular mortality, morbidity, and rehospitalization [33].…”
Section: Discussionmentioning
confidence: 66%
“…These interventions may be highly relevant to restore preisolation physical activity levels and to counteract the negative effects of inactivity on the cardiovascular system. In this scenario, remotely supervised home-based interventions have been shown to significantly improve physical fitness in coronary artery disease and heart failure patients (2,3,40,42) and to be equally effective in center-based interventions for secondary prevention (2). This type of training has shown to be safe for stable low-tomoderate risk cardiac patients and hypertensive individuals (26,40,42,49).…”
mentioning
confidence: 99%
“…The group size is based on an anticipated increase of cardiorespiratory fitness 2.8 mL/kg/min with a standard deviation of 4.3 mL/kg/min from the previous study. [ 16 ] Seventy-six participants will need to be included in the study to achieve 80% statistical power at 5% statistical significance. The drop-out rate in follow-up at 12 week and follow-up is taken into account, that is, 38 participants need to be randomized to the experimental and control arm of the study.…”
Section: Methodsmentioning
confidence: 99%
“…A recently completed study demonstrated an intervention using the HR monitor and internet as an effective and sufficient way of providing telerehabilitation in patients after CHD. [ 16 ] A 12-week home-based program showed that telerehabilitation leads to similar results in cardiopulmonary fitness as outpatient training. Although this study proved the feasibility and efficiency of telerehabilitation, further randomized control studies are needed in this field.…”
Section: Introductionmentioning
confidence: 99%